Role of Glucose Metabolism Reprogramming in the Pathogenesis of Cholangiocarcinoma - Pant, Kishor; Richard, Seth; Peixoto, Estanislao; Gradilone, Sergio A (Frontiers in Medicine, 2020)
Cholangiocarcinoma (CCA) is one of the most lethal cancers, and its rate of occurrence is increasing annually. The diagnoses of CCA patients remain elusive due to the lack of early symptoms and is misdiagnosed as HCC in a considerable percentage of patients. It is crucial to explore the underlying mechanisms of CCA carcinogenesis and development to find out specific biomarkers for early diagnosis of CCA and new promising therapeutic targets. In recent times, the reprogramming of tumor cells metabolism has been recognized as a hallmark of cancer. The modification from the oxidative phosphorylation metabolic pathway to the glycolysis pathway in CCA meets the demands of cancer cell proliferation and provides a favourable environment for tumor development. The alteration of metabolic programming in cancer cells is complex and may occur via mutations and epigenetic modifications within oncogenes, tumor suppressor genes, signaling pathways, and glycolytic enzymes. Herein we review the altered metabolism in cancer and the signalling pathways involved in this phenomena as they may affect CCA development. Understanding the regulatory pathways of glucose metabolism such as Akt/mTOR, HIF1α, and cMyc in CCA may further develop our knowledge of this devastating disease and may offer relevant information in the exploration of new diagnostic biomarkers and targeted therapeutic approaches for CCA.